Pendampingan Hukum Bagi Perempuan dan Anak Pasca Cerai oleh Tim Advokat Profit: Studi Kasus di Pengadilan Agama Pati Perkara Nomor 778/Pdt.G/2024/PA.Pt - Hasanah, Lailatul Nur (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to find out and analyze legal assistance for women and children by a team of advocates at the Pati Religious Court. The rights of women and children are one of the obligations of an ex-husband after divorce, namely providing iddah support, muta'ah and madhiyyah support as well as costs. Education for children from underage to adulthood is the responsibility of a wife. So that in the divorce divorce case carried out by the husband at the Pati religious court, the team of advocates received attention. The research method used in this writing is empirical juridical, with the specifications of this research using qualitative descriptive research, legal assistance for women and children by the profit advocate team is felt by the profit advocate team to be less than optimal, especially considering the situation of the client, who is the Defendant and The client is just a housewife. In this case, advocates as legal representatives provide legal assistance to women and children after divorce free of charge in order to obtain equal justice or equality before the law. This aims to uphold the principles of civil procedural law within the scope of the Pati religious court, and the team profit advocate in Pati district. However, in reality, this matter is not paid enough attention by law enforcers who are profit advocates in Pati district. And it is hoped that this is a form of service effort by the profit advocate team in accordance with the advocate's oath in accordance with article 4 of the Law of the Republic of Indonesia Number 18 of 2003 concerning Advocates in conjunction with the letter from the chairman of the Supreme Court of the Republic of Indonesia Number: 73KMA/HK.01/IX/2015 September 25 2015 regarding the oath of lawyers.